DEVELOPMENT OF OPERATION PROCESS MAP AND ANALYSIS OF INVENTORY CONTROL BASED ON MATERIAL REQUIREMENT PLANNING IN ASSEMBLY LINE - Annisa Indah Pratiwi; Afif Hakim; Ragil Yuli Santosa (Journal of Industrial Engineering and Halal Industries, 2020)
Production planning and control is a theory which discusses all the activities that take place in a production process which includes product planning, costs, production processes, scheduling, forecasting demand and many other products. Planning the amount of inventory that will be owned company is one of the problems often faced by companies. Especially when the inventory is one important factor that can support the company's production processes and help meet customer demand. For companies that have strategies make to stock, inventory can have a major impact on the pricing of the product or the company's finances. Appropriate inventory management can be one of the keys to minimize and optimize the company's costs to be incurred. Determination lot size in MRP is a complex and difficult problem. Lot size is defined as a quantity stated in the order acceptance and delivery of orders in the MRP. Decisions about the size of the lot and when production is very important because it involves the use of labor and equipment are economical. Based on observations there are 13 components which are arranged in the trolley assembly process and are divided into 4 work stations in the production process. After making a map process operations per each work station, the cycle time for 1800 seconds is obtained. Based on data analysis about inventory costs for each component, it can be seen that the calculation using the EOQ method is the method that produces the calculation results with the largest value of Rp. 111,000,500, - then for the L4L and POQ methods produce the calculation results that have the same value of Rp. 16,200,000. Then the decision taken is to choose the L4L method because with this technique can produce exactly how many raw materials needed.